A highly concentrated diet increases biogas production and the agronomic value of young bull's manure - Silva de Mendonca Costa, Monica Sarolli; Lucas, Jorge de [UNESP]; Mendonca Costa, Luiz Antonio de; Amorim Orrico, Ana Carolina (Elsevier B.V., 2016)
The increasing demand for animal protein has driven significant changes in cattle breeding systems, mainly in feedlots, with the use of young bulls fed on diets richer in concentrate (C) than in forage (F). These changes are likely to affect animal manure, demanding re-evaluation of the biogas production per kg of TS and VS added, as well as of its agronomic value as a biofertilizer, after anaerobic digestion. Here, we determined the biogas production and agronomic value (i.e., the macronutrient concentration in the final biofertilizer) of the manure of young bulls fed on diets with more (80% C + 20% F; 'HighC' diet) or less (65% C + 35% F; 'LowC' diet) concentrate, evaluating the effects of temperature (25, 35, and 40 degrees C) and the use of an inoculum, during anaerobic digestion. A total of 24 benchtop reactors were used, operating in a semi-continuous system, with a 40-day hydraulic retention time (HRT). The manure from animals given the HighC diet had the greatest potential for biogas production, when digested with the use of an inoculum and at 35 or 40 degrees C (0.6326 and 0.6207 m(3) biogas/kg volatile solids, or VS, respectively). We observed the highest levels of the macronutrients N, P, and K in the biofertilizer from the manure of animals given HighC. Our results show that the manure of young bulls achieves its highest potential for biogas production and agronomic value when animals are fed diets richer in concentrate, and that biogas production increases if digestion is performed at higher temperatures, and with the use of an inoculum. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Temperature; Inoculum; Semi-continuous; Digestate